Using Kanban to Reshape Communication and Collaboration Across Teams - Rodrigues, Eriky; Mesquita, Laleska; Costa, Arthur Lucca; Sampaio, Matheus; Caetano, Rogério (Anais Estendidos do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais Estendidos do XXI Simpósio Brasileiro de Sistemas Colaborativos, 2026)
Communication and collaboration remain challenges in software teams in contexts that require coordination across multiple actors. Visual workflow approaches such as Kanban may support in implementing organizational changes. In this sense, we implemented Kanban within a project documentation team. Then, we conducted an empirical study using a questionnaire in which participants rated communication and collaboration before and after Kanban adoption and justified their assessments. We found statistically significant improvements in perceived communication and collaboration after Kanban adoption, and our qualitative findings suggest that increased work visibility, the use of visual resources, and reduced dependence on intermediary communication contributed to these improvements. We also highlight our lessons within this experience, which we expect to help practitioners understand potential benefits associated with Kanban adoption.